Personality-based intercultural awareness in undergraduate translation students via postcrossing - Shelestova, T.Yu.; Kalizhanova, A.N.; Bedelbayeva, M.V. (Cogent Arts & Humanities, 2024)
The study examines the necessity of a sustainable research network for transformative education, focusing on the Postcrossing phenomenon to analyze cross-cultural dynamics through authentic postcards. A mixed-methods approach was used, including a Postcrossing postcard-based questionnaire and personality assessment. The results highlight a significant relationship between personality types and intercultural interpretation skills, particularly among iNtuitive Thinking and iNtuitive Feeling types. This research demonstrates the potential of utilizing Postcrossing in translation studies and educational psychology to promote personality-based intercultural awareness.
Keywords: Postcrossing postcards; undergraduate translation students; intercultural awareness; personalitybased types